Advanced Micro & Nanosystems Vol.4 : Microengineering of Metals and Ceramics - [Tidak Terdaftar] (Wiley -VCH Verlag GmbH, 2005)
Advanced Micro & Nanosystems Vol.4 : Microengineering of Metals and Ceramics